The Role Of Human Resources Accounting In The Valuation Of Human Capital - soltani, adel (Journal of Research in Finance and Accounting, 2021)
This research aims to highlight the contribution of human resources accounting to the valuation of human capital, This study analyzed the prospects and challenges of valuing human capital through Human Resource Accounting (HRA) using a descriptive and analytical approach based on a study case in an important Algerian private company (CONDOR ELECTRONICS). The study concluded that Human Resource Accounting (HRA) fulfils the need of evaluation human resources but The contribution of HRA is however limited by lack of universal approach to its reporting and low level of awareness and acceptance of the techniques. But it remains to say that every organization may use one of these models to use the information regarding human capital in managing it as chewed through the study case.